THE PROFILE OF ENGLISH TEACHERS’ PROFESSIONAL COMPETENCE AND STUDENTS’ ACHIEVEMENT AT SMA NEGERI 1 ENREKANG - Umiyati Jabri (Edumaspul: Jurnal Pendidikan, 2017)
This research was aimed at identifying the profile of English teachers’ professional competence and students’ achievement at SMK Negeri 1 Makassar. The profile of English teachers’ professional competence was specified based on the two sub-competences in the National Standard of Education, in section 28, sub-section 3 point c. The researchers employed descriptive evaluation method. The population of this research was English teachers of SMK Negeri 1 Makassar. The sample was purposive sampling technique in which researcher chose the three certified English teachers as the sample. They were observed in the classroom while teaching and learning process and were also interviewed in relation to the implementation of professional competence in their teaching. The result showed for the first sub- competence, the teachers show their effort in selecting, determining, and organizing the materials by making their own module. In terms of the second sub-competence, all of the teachers have less effort in developing their professional competence. It can be concluded that the three English teachers still need more improvement. in terms of students’ achievement, the data from findings indicates that the highest students’ score is from teacher III. Meanwhile, the highest score of teacher professional competence among those teachers is teacher I. It indicates that many factors such as intelligence type, motivation, attitude, and condition of learning taking place that could affect the students’ achievement, not only the professional competence.